Sex-related differences in muscular factors previously identified in the literature as potentially associated with hamstring strain injury in professional football players - Rodrigues, L. G.; Vianna, K. B.; de Oliveira, N. T.; de Carvalho Chaves, A.; Severo-Silveira, L.; Ribeiro-Alvares, J. B.; Carvalho, P.; Baroni, B. M. (Sport Sciences for Health, 2023)
Purpose The purpose of this study was to assess if differences in hamstring strength, hamstring-to-quadriceps (H:Q) strength ratio, and biceps femoris long head (BFLH) fascicle length exist between male and female professional football (soccer) players.